Psychosomatic Medicine - Jáuregui Lobera, Ignacio (IntechOpen, 2020)
Modern psychosomatic medicine is a comprehensive framework for a holistic (biopsychosocial) perspective of illnesses and patient care. It highlights the influence of psychosocial factors on health, the interaction between psychosocial and biological factors in the course and outcome of diseases, and a whole perspective with respect to treatments. This book discusses holistic approaches to both organic and psychopathological diseases. Over three sections, authors address psychosomatic approaches to fibromyalgia, palliative care, anxiety and depression, obesity, and traumatic stress disorders.